Daytime melatonin levels in saliva are associated with inflammatory markers and anxiety disorders. (February 2020) - Sundberg, Isak; Rasmusson, Annica J.; Ramklint, Mia; Just, David; Ekselius, Lisa; Cunningham, Janet L.
Highlights: We analyzed daytime saliva melatonin in relation to levels of 72 inflammatory markers. Melatonin levels at 11:00 were correlated with CD 5. Melatonin after lunch was correlated with MCP-1, MIP-1α and VEGF-A. Melatonin after lunch, VEGF-A and MIP-1α was associated with anxiety disorders. Abstract: Background: The bidirectional interaction between melatonin and the immune system has largely gone unexplored in a clinical context and especially in a psychiatric population. This study explored the association between melatonin during the day and inflammatory cytokines in young adult patients seeking psychiatric care. Methods: Samples and data were collected from 108 young adults (mean age 21, SD = 2) at an outpatient clinic for affective disorders. Daytime saliva melatonin levels were analyzed with enzyme-linked immunosorbent assay (ELISA) in relation to normalized serum expression levels of 72 inflammatory markers in a proximity extension assay (PEA). In a post hoc analysis the markers associated with melatonin were tested in a generalized linear model to see whether there is a relationship to anxiety disorder or depression. Results: After Bonferroni correction for multiple testing, melatonin levels at 11:00 were positively correlated with CD5 ( p  = 4.2e-4). Melatonin levels after lunch were correlated with CCL2/MCP-1 ( p  = 4.2e-4), CCL3/MPI-1α ( p  = 6.5e-4) and VEGF-A ( p  = 5.3e-6). In the generalized linear model, positive associations were found for the presence of any anxiety disorder with melatonin after lunch ( p  = 0.046), VEGF-A ( p  = 0.001) and CCL3/MPI-1α ( p  = 0.001). Conclusion: Daytime saliva levels of melatonin were related to several inflammatory markers in young adults with psychiatric disorders. This observation likely reflects the bidirectional relationship between melatonin production and the immune system. These findings may have relevance for the understanding of psychiatric disorders and other conditions associated with low-grade inflammation.